Zōon polithikon and His State - Chlewicki, Maciej (Sensus Historiae, 2020)
In this article, the author discusses a particular concept of state called here “civil (or citizen) state”. The idea of civil (citizen) state is of exceptional importance in the Western tradition because of its ancient origins and current practical significance as well as due to theoretical-philosophical ground of this concept. According to the author of the article, idea of civil state deserves particular attention also because of an evident direct relevance of such notions as: state, politics, citizen, which is not included in other concepts of state and politics. This non coincidental relevance of the mentioned notions demonstrates that we can speak in the case of this notion of a kind of the concept of state in its essential meaning and for that very reason, the idea of civil state stands in favor in the Western tradition present inthe modern age and contemporary times also. The author of the article clarifies the role of the mentioned idea of state in Western thought and refers to the concept of human being defined as zōon politikon.